A Neat Methanol Fed Passive DMFC with a New Anode Structure. Issue 3 (17th May 2017) - Zhang, F.; Jiang, J.; Zhou, Y.; Xu, J.; Huang, Q.; Zou, Z.; Fang, J.; Yang, H.
Abstract: A passive direct methanol fuel cell (DMFC) with a novel anode structure and operated in neat methanol is reported. The anode incorporates a methanol barrier that is composed of a methanol‐resisting pervaporation film (PVF), a buffer cavity and a water‐resisting PVF. The new anode allows for control of the rate of methanol transportation from the fuel tank to the anodic side of the membrane electrode assembly (MEA) and for retention of water recovered from the cathode to the anode, issuing an efficient anodic reaction and a high proton‐conduction of the Nafion membrane. Such a passive DMFC fed with neat methanol reaches a maximal power density of 29.0 mW cm −2 and an energy efficiency of 23.1%, in comparison with a DMFC with a single methanol‐resisting PVF (energy efficiency = 7.8%). The performance of the passive DMFC system remained constant over 400 h of continuous operation.